Food Processed Product Development Training Based on Village Potential : Pelatihan Pengembangan Produk Olahan Pangan Berbasis Potensi Desa - Rina Susanti; Tudji Santoso; Yuli Hesman; Wini Indrianti; Siti Rahmah (Yayasan Ahmar Cendekia Indonesia, 2022)
The implementation of community service in the form of training in the development of processed food products based on village potential which has the aim of developing village potential through processed food products which can be an idea for business opportunities so that they can indirectly build the community's economy as well as poverty alleviation. Bina Baru Village, Kampar Kiri Tengah District, Kampar Regency is a village where community service is located and is the target for community service. The form of the activity program from the service team is training on the development of processed food products which is carried out on a scale. The results of the training activities that produce processed food products consist of 3 products, namely Tofu Chips, Tempe Nuggets and Spinach Sticks. The conclusion is that the service goes according to plan and the community has a source of income from processed food products. Abstrak Pelaksanaan pengabdian kepada masyarakat berupa pelatihan pengembangan produk olahan pangan berbasis potensi desa yang memiliki tujuan mengembangkan potensi desa melaui produk olahan pangan yang dapat menjadi ide peluang usaha sehingga bisa membangun perekonomian masyarakat secara tidak lansung sekaligus sebagai penanggulangan kemiskinan. Desa Bina Baru Kecamatan Kampar Kiri Tengah Kabupaten Kampar merupakan desa lokasi pengabdian dan yang menjadi sasaran pelaksanaan pengabdian kepada masyarakat. Bentuk program kegiatan dari tim pengabdian adalah pelatihan pengembangan produk olahan pangan yang dilakukan secara berskala. Hasil kegiatan pelatihan yang menghasilkan produk olahan pangan yang terdiri dari 3 produk yaitu Kripik tahu, Nugget Tempe dan Stik Bayam. Simpulan bahwa pengabdian berjalan sesuai rencana dan masyarakat memiliki sumber pendapatan dari hasil olahan pangan.